Using aminopyrine as a nitrogen-enriched small molecule precursor to synthesize high-performing nitrogen doped mesoporous carbon for catalyzing oxygen reduction reaction. Issue 2 (3rd January 2017) - Zhang, Enguang; Wu, Mingjie; Tang, Qiaowei; Gong, Qiaojuan; Sun, Shuhui; Qiao, Jinli; Zhang, Lei
Abstract : With aminopyrine as a nitrogen-enriched small molecule precursor, a series of nitrogen doped carbon materials have been fabricated and explored as electrocatalysts for oxygen reduction reaction (ORR). Abstract : With aminopyrine as a nitrogen-enriched small molecule precursor, a series of nitrogen doped carbon materials have been fabricated and explored as electrocatalysts for oxygen reduction reaction (ORR). The most active catalyst is a nitrogen doped carbon, which was prepared through a facile template-mediated pyrolyzing method using ferric nitrate (Fe(NO3 )3 ·9H2 O) as an activation reagent along with nanoscaled silica as a sacrificial support (hereafter referred to as AP/SiO2 ). The AP/SiO2 is confirmed and identified as having highly active molecule catalytic centers for ORR, due to its possessing a porous, sponge-like and uniform structure with a super-large specific surface area of 932.68 m 2 g −1 . The AP/SiO2 catalyst exhibited a high onset potential of 0.98 V, a half-wave potential of 0.82 V, and a high number of exchanged electrons (>3.8, close to four) in alkaline media. After 5000 continuous cycles, the material showed almost no negative shift with respect to the Pt/C material. Even in acidic medium, the AP/SiO2 catalyst still showed much higher durability than Pt/C and a low yield of HO2 − . This work may have provided a new and simple route in the design and batch-synthesis of highly active and durable carbonaceous electrocatalysts for ORR.